PENGARUH WORK LIFE BALANCE DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA RSUD LAKIPADADA TANA TORAJA - Tangkeallo, Dian Intan (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
Work life balance became one of the triggers in job satisfaction. The aim of the research was to determine the effect of work life balance and compensation on employees’ work satisfaction and performance in Lakipadada Regional Public Hospital of Tana Toraja Regency. The research was a causal explanatory relation. The population and sample were all nurses in Lakipadada Regional Public Hospital of Tana Toraja Regency. The sample was selected using non probability sampling method with purposive sampling technique. The data were analyzed using path analysis. The results of the research indicate that (1) word life balance has a positive and significant effect on nurses’ work satisfaction in Lakipadada Regional Public Hospital of Tana Toraja Regency, so the hypothesis is accepted, (2) the result of analysis on the direct effect of compensation on work satisfaction in Lakipadada Regional Public Hospital of Tana Toraja Regency indicates that there is a positive and significant effect on employees’ performance, so the hypothesis is accepted, (3) work life balance positively has a direct effect on employees’ performance in Lakipadada Regional Public Hospital of Tana Toraja Regency, so the hypothesis in this research is accepted, (4) compensation positively and significantly has a direct effect on employees’ performance in Lakipadada Regional Public Hospital of Tana Toraja Regency, so the hypothesis in this research is accepted.